Interferon-gamma expression by Th1 effector T cells mediated by the p38 MAP kinase signaling pathway. - Rincón, M (1998)
Signal transduction via MAP kinase pathways plays a key role in a variety of cellular responses, including growth factor-induced proliferation, differentiation and cell death. In mammalian cells, p38 MAP kinase can be activated by multiple stimuli, such as pro-inflammatory cytokines and environmental stress. Although p38 MAP kinase is implicated in the control of inflammatory responses, the molecular mechanisms remain unclear. Upon activation, CD4+ T cells differentiate into Th2 cells, which potentiate the humoral immune response or pro-inflammatory Th1 cells. Here, we show that pyridinyl imidazole compounds (specific inhibitors of p38 MAP kinase) block the production of interferon-gamma (IFNgamma) by Th1 cells without affecting IL-4 production by Th2 cells. These drugs also inhibit transcription driven by the IFNgamma promoter. In transgenic mice, inhibition of the p38 MAP kinase pathway by the expression of dominant-negative p38 MAP kinase results in selective impairment of Th1 responses. In contrast, activation of the p38 MAP kinase pathway by the expression of constitutivelyactivated MAP kinase kinase 6 in transgenic mice caused increased production of IFNgamma during the differentiation and activation of Th1 cells. Together, these data demonstrate that the p38 MAP kinase is relevant for Th1 cells, not Th2 cells, and that inhibition of p38 MAP kinase represents a possible site of therapeutic intervention in diseases where a predominant Th1 immune response leads to a pathological outcome. Moreover, our study provides an additional mechanism by which the p38 MAP kinase pathway controls inflammatory responses.